SOX10 is as specific as S100 protein in detecting metastases of melanoma in lymph nodes and is recommended for sentinel lymph node assessment. (September 2020) - Szumera-Ciećkiewicz, Anna; Bosisio, Francesca; Teterycz, Paweł; Antoranz, Asier; Delogu, Francesco; Koljenović, Senada; van de Wiel, Bart A.; Blokx, Willeke; van Kempen, Léon C.; Rutkowski, Piotr; Christopher van Akkooi, Alexander; Cook, Martin; et al.
Abstract: Background: Sentinel lymph node (SLN) biopsy remains crucial for melanoma staging. The European Organisation for Research and Treatment of Cancer Melanoma Group recommends performing immunohistochemical stainings for reproducible identification of melanoma metastases. S100 protein (pS100) is a commonly used melanocytic antigen because of its high sensitivity in spite of relatively low specificity. SRY-related HMG-box 10 protein (SOX10) is a transcription factor characterising neural crest-derived cells. It is uniformly expressed mostly in the nuclei of melanocytes, neural, and myoepithelial cells. Pathologists sometimes prefer SOX10 as a melanoma marker, but it has not yet been investigated on a large-scale to confirm that it is reliable and recommendable for routine SLN evaluation. Methods: Four hundred one treatment-naïve lymph node (LN) metastatic melanomas were included in high-density tissue microarrays and were assessed for the presence of SOX10 and pS100 by immunohistochemistry. The slides were digitalised, shared and evaluated by a panel of experienced melanoma pathologists. Results: The vast majority of melanomas were double-positive for pS100 and SOX10 (93.2%); a small percentage of the cases (3.9%) were double-negative melanomas. Discordance between the two markers was observed: 1.9% pS100(−)/SOX10(+) and 0.75% pS100(+)/SOX10(−). SOX10 was not expressed by immune cell types in the LN, resulting in a less controversial interpretation of the staining. Conclusions: SOX10 is as equally specific as pS100 for the detection of melanoma metastases in LNs. The interpretation of SOX10 staining is highly reproducible among different centres and different pathologists because of the absence of staining of immune cells. Highlights: SOX10 is a highly specific marker for melanoma metastasis in lymph nodes (LNs), comparable with pS100. SOX10 is highly reproducible and easily interpretable if a ready-to-use antibody is used. SOX10 has the same level of recommendation as pS100 for the detection of melanoma metastasis in SLN protocols.